Who needs to solve the vegetarian men dilemma? - Bogueva, Diana; Marinova, Dora (2020)
Rebranding men’s dietary choices in the mind of the mainstream Australians to include more plant-based options, is a difficult task. Eating meat is a way to satisfy nutritional requirements but also has an embedded symbolism of power to which Australian men are accustomed. Vegetarian men are seen by the majority of the male population and the social discourse surrounding gendered food as betraying the social expectations about masculine behavior despite research showing the need for higher intake of fiber to reduce non-communicable diseases and improve planetary health. Those who have adopted vegetarian diets are exposed to ridicule and may face social isolation because of their unorthodox food choices. In order to reshape the meat consumption of men in Australia, we must recognize the gendered dynamics of dietary choices that associate meat consumption with masculinity.